EMPLOYEE PERFORMANCE AFFECTED BY WORK FROM HOME (WFH) AND CREATIVITY DURING THE PANDEMIC IN YPKPM AMBON FOUNDATION - Paais, Maartje; Souhoka, Semuel (jfpublisher, 2022)
This research aims to analyze the effect of Work from Home (WFH) and creativity on teacher performance during the Covid pandemic in YPKPM Ambon Foundation. The population of this research is 130 people and the sample is 57 people. The test conducted through multiple linear analysis techniques. The hypothesis testing results obtained that WFH has a value of tcount > ttable that is 3.238 > 1.671 with a significant level of 0.002 <0.05, creativity has a value of tcount > ttable that is 2.485 > 1.671 with a significant level of 0.016 < 0.05. It means WFH and creativity have a positive and significant effect on the teacher performance in YPKPM Ambon Foundation. The results of the simultaneous test showed that the value of Fcount> Ftable was 39.139 > 3.15 with a significant level of 0.000 < 0.05, then it concluded that WFH and creativity had a significant and effect on the teacher’s performance at Ambon YPKPM Foundation. The coefficient of determination test obtained an adjusted r square value of 0.592 or 59.2%, which means that WFH and creativity only explain variations in teachers’ performance variables by 59.2% and the remaining 40.8% is influenced by other variables outside of this research variable.